Effect Of The Use Of Teaching Model Induces Changes In Concepts Simson Tarigan On Chemistry Student Learning Outcomes In Senior High School Class X - Silitonga, Friska Septiani; Tarigan, Simson (Program Studi Pendidikan Kimia, Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2015)
A study of the use of teaching models induces changes in concepts Simson Tarigan on chemistry student learning outcomes has been conducted to determine student learning outcomes of students taught using teaching models induced changes in concepts Simson Tarigan. The population in this study were all students of class X SMA Negeri 3 Medan 2011/2012 academic year consists of six classes, sampling technique was randomly. The sample consisted of two classes where the class X.5 as grade control using conventional learning models and X.6 class as a class experiment using the model of teaching induces changes in concept Samson Tarigan. Each class sample was of 40 people. Instruments used as a data collection tool that tests of learning outcomes in the form of 20 multiple choice questions (validated) with the answer choices as much as five choices (A, B, C, D, and E). Data were analyzed using the computer Excel programme, includes a description of the data, normality, homogenity, and hypothesis testing. The analysis of the data obtained by the average value of the initial test scores (pre-test) experimental class students obtained at 35.75 with a standard deviation of 8.589 and the average post-test scores obtained at 82 with a standard deviation of 6.28, while in the control class that the average test score initial (pre-test) students at 37.125 with a standard deviation of 10.675 and the average post test score obtained at 75.625 with a standard deviation of 5.087. Based on hypothesis testing was done by using the t-test (testing the right side) with Î±= 0.05 was obtained t (4.988) > t table (1.6671), in other words the learning outcomes was in the category of high learning outcomes (G=72%) and the control class that learning outcomes in the middle category (G=61.2%). This show that was outside the reception Ho, then based on these tests showed that Ho was rejected and means Ha accepted, so it could be stated that the results of studying chemistry students who are taught by the teaching models induces changes in concept Simson Tarigan higher learning outcomes chemistry students chemistry student takut taught higher than learning outcomes chemistry of students taught by conventional methods.